2015
DOI: 10.1007/s11356-015-5609-x
|View full text |Cite
|
Sign up to set email alerts
|

Quinolone co-resistance in ESBL- or AmpC-producing Escherichia coli from an Indian urban aquatic environment and their public health implications

Abstract: Quinolone and β-lactam antibiotics constitute major mainstay of treatment against infections caused by pathogenic Escherichia coli. Presence of E. coli strains expressing co-resistance to both these antibiotic classes in urban aquatic environments which are consistently being used for various anthropogenic activities represents a serious public health concern. From a heterogeneous collection of 61 E. coli strains isolated from the river Yamuna traversing through the National Capital Territory of Delhi (India),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 34 publications
5
17
0
Order By: Relevance
“…Such global dissemination of the CTX-M type ESBLs has primarily been attributed to the extremely mobilizable genetic platforms which harbor bla CTX-M genes ( Cantón et al, 2012 ), association of these platforms with E. coli genotypes showing clonal dissemination ( Coque et al, 2008 ; Nicolas-Chanoine et al, 2008 ; Woodford et al, 2011 ), and frequent co-existence of bla CTX-M with genes conferring resistance to other classes of antibiotics like fluoroquinolones and aminoglycosides leading to high rates of co-selection ( Cantón and Ruiz-Garbajosa, 2011 ; Bajaj et al, 2015 ). Analysis of the genetic environments of bla CTX-M genes has revealed that the promoter sequence present in the upstream region significantly affects gene expression as well as its dissemination (summarized in Table 1 ).…”
Section: β-Lactamases Of Critical Concernmentioning
confidence: 99%
“…Such global dissemination of the CTX-M type ESBLs has primarily been attributed to the extremely mobilizable genetic platforms which harbor bla CTX-M genes ( Cantón et al, 2012 ), association of these platforms with E. coli genotypes showing clonal dissemination ( Coque et al, 2008 ; Nicolas-Chanoine et al, 2008 ; Woodford et al, 2011 ), and frequent co-existence of bla CTX-M with genes conferring resistance to other classes of antibiotics like fluoroquinolones and aminoglycosides leading to high rates of co-selection ( Cantón and Ruiz-Garbajosa, 2011 ; Bajaj et al, 2015 ). Analysis of the genetic environments of bla CTX-M genes has revealed that the promoter sequence present in the upstream region significantly affects gene expression as well as its dissemination (summarized in Table 1 ).…”
Section: β-Lactamases Of Critical Concernmentioning
confidence: 99%
“…Ciprofloxacin resistance was 29.5% in ESBL positive and 4.7% in ESBL-negative isolates and this difference was significant (p= <0.01), an indication that ciprofloxacin resistance in the isolates was closely associated with ESBLs (Shaikh et al, 2015). Common co-resistance has been found in ESBL-producing organisms to aminoglycosides, fluoroquinolones, tetracyclines, chloramphenicol, and sulfamethoxazole-trimethoprim (Bajaj et al, 2016). This is a demonstration of the emergence of epidemic clones harbouring several beta-lactamases simultaneously (Bla CTX-M , Bla SHV and Bla TEM ) and perhaps of other mechanisms of resistance.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, some studies point to the idea that ARGs involved in the expression of aminoglycoside-modifying and β-lactamase enzymes were present in the environment long before the use manmade antibiotics in a therapeutic scope [47,48,49] showed that βlactamase family shared a common origin with enzymes involved in cell wall biosynthesis. In spite of using the antibiotics and their presence in the environment, bacteria resistant to β-lactams are thriving and there are a constant presence in more and more countries [50,51,52]. The same emerging resistance pattern it is also observed for bacteria producing carbapenemase [53,54,55].…”
Section: Enzymatic Degradation Of Antibioticsmentioning
confidence: 99%